Research of online dynamic weighing system of coal - LI Ping; WANG Yan-wen (Gong-kuang zidonghua, 2013)
The paper analyzed weighing principle and advantages and disadvantages of current online dynamic weighing system of coal, namely dynamic weighing system of belt scale, mine car scale and skip scale, and proposed a weighing system of mine car scale based on image processing technology with high measurement precision. It researched key problems of online dynamic weighing system of coal, namely calibration method, weighing sensor, dynamic mathematical model, data processing algorithm and software of upper computer system, and indicated that improving calibration precision and reducing calibration difficulty would be research direction of calibration method of online dynamic weighing system of coal; vibration string weighing sensor would be development direction of weighing sensor in future; advanced technology and theory would be research direction of dynamic mathematical model and data processing algorithm.